Percutaneous ultrasound-guided core needle biopsy for the diagnosis of cardiac tumors: Optimizing the treatment strategy for patients with intermural and pericardial cardiac tumors - Xie, Ying; Hong, Zhi-liang; Zhao, Yan-chun; Chen, Sheng; Lin, Yu-cheng; Wu, Song-song (Frontiers in Oncology, 2022)
Objective To investigate the clinical value and practical safety of ultrasound-guided percutaneous core needle biopsy on diagnosing cardiac tumor and to discuss the treatment strategy for cardiac intermural and pericardial tumors. Methods The clinical data were retrospectively collected for patients with intermural and pericardial cardiac tumors. The patients were divided into groups of surgical resection, surgical resection after obtaining pathological tissue by PUS-CNB and/or radiotherapy according to the treatment modality. Ultrasound-guided aspiration biopsy was divided into cardiac tumor biopsy and extracardiac lesion biopsy according to patient conditions. The surgical time was recorded, and the safety and clinical application value of PUS-CNB for the diagnosis of cardiac tumors were evaluated in terms of complications and satisfaction with pathological sampling. Results A total of 18 patients cases were collected, and PUS-CNB of cardiac tumors was performed in 8 cases, with sampling times averaging 15.6±3.0 min. Four cases of cardiac tumors combined with extracardiac tumors were biopsied, with puncture times averaging 13.0±2.9 min. All 12 biopsied patients had no postoperative complications. Except for 1 failed biopsy, the biopsies were successful and the pathological results were consistent with the clinical diagnosis with an satisfaction rate of 91.7%. Except for 2 cases of surgical resection, the rest were considered for conservative treatment. Surgical resection and/or biopsy were performed in 6 cases, and 2 cases aggravated after surgery. The final pathology of all 17 cardiac tumors was malignant. Conclusion PUS-CNB is safe and effective, providing a simple and undemanding method for accurate diagnosis of cardiac intermural and pericardial tumors whilst avoiding unnecessary open-heart surgery.